China's regional income inequality and its main determinants. - Cher, Huey Wen. (2008)
This paper attempts to explain the trend in regional income inequality in China using 30 provinces for the period from 1978 to 2006 by constructing Theil indices. In general, a U-shaped trend is identified and we decomposed the inequality to explain the trend. It is found that within region inequality has been decreasing while between regions inequality has been increasing. The paper has also identified inequalities in government expenditure, human capital accumulation and share of SOE gross industrial output as the primary determinants in income inequality in China.